The effect of a low-carbohydrate diet on periodontal health and inflammation in patients with type 2 diabetes - Hiroj S Bagde; Mohammad K Alam; Abdullah Khalid A Alhamwan; Hamed Muhanned H Aljubab; Faisal Fraih A Alrashedi; Dhari Hameed M Aljameeli; Mohammed G Sghaireen (Wolters Kluwer Medknow Publications, 2024)
Background: The interaction between type 2 diabetes and periodontal disease underscores the importance of exploring dietary interventions that could mitigate inflammation and improve periodontal health in diabetic patients. Materials and Methods: This randomized controlled trial included 100 patients with type 2 diabetes who were equally divided into two groups: Group A (low-carbohydrate diet) and Group B (control group). Patients in Group A followed a low-carbohydrate diet for 12 weeks, while Group B maintained their regular dietary habits. Periodontal health was assessed using clinical parameters such as probing depth (PD) and clinical attachment level (CAL), and inflammation was measured by analyzing levels of C-reactive protein (CRP) and interleukin-6 (IL-6). Statistical analyses were performed using appropriate tests. Results: After 12 weeks, Group A exhibited significant improvements in periodontal health compared to Group B. The mean PD reduction was 0.5 mm in Group A and 0.1 mm in Group B, with a corresponding mean CAL gain of 0.3 mm in Group A and no significant change in Group B. Inflammatory markers also showed favorable outcomes in Group A, with a decrease of 1.2 mg/L in CRP levels and 20% reduction in IL-6 levels. In contrast, Group B demonstrated minimal changes in inflammatory markers. The differences in PD, CAL, CRP, and IL-6 levels between the two groups were statistically significant (P < 0.05). Conclusion: The adoption of a low-carbohydrate diet for 12 weeks demonstrated significant improvements in periodontal health and reduction of inflammation in patients with type 2 diabetes.